Review of Improving Refrigeration Machine Performance by Adding Nanoparticles to the Refrigeration System Using Computational Fluid Dynamics (CFD) Simulation and Comparing it with Experimental Results - Irwansyah, Dandi (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
In this journal, the author reviews the performance improvement of vapor compression refrigeration machines by adding nanoparticles into the refrigeration system using CFD simulation. This study aims to determine the improvement of refrigeration machine performance by adding nanoparticles into the refrigeration system using CFD simulation and to compare the simulation results with the experimental results. Where the method used in this study is a literature review. The results of the literature study show that the dispersion of nanoparticle additives can affect the increase in the refrigeration system performance coefficient (COP) and can maximize thermal conductivity, heat transfer coefficient, and other heat transfer characteristics so that it can produce lower power consumption. Using the CFD simulation method, the highest increase in refrigeration system performance was obtained through the simulation of SiO2 + R134a nano refrigerants with a volume concentration of 4% and an increase value of 22.58%. From the experimental results, the highest value was obtained by Al2O3 + R134a nano refrigerants with a volume concentration of 0.5% and an increased value of 30.85%. The system's performance showed a significant improvement with the addition of nanoparticles. Therefore, the performance of the refrigeration machine with the addition of nanoparticles in the refrigerant fluid is higher than the system using pure refrigerant fluid (without nanoparticles).